2000
DOI: 10.2337/diacare.23.6.754
|View full text |Cite
|
Sign up to set email alerts
|

Health care and health status and outcomes for patients with type 2 diabetes.

Abstract: OBJECTIVE -To evaluate access and utilization of medical care, and health status and outcomes that would be influenced by recent medical care, in a representative sample of patients with type 2 diabetes. RESEARCH DESIGN AND METHODS-A national sample of 733 adults with type 2 diabetes was studied from 1991 to 1994 in the Third National Health and Nutrition Examination Survey. Structured questionnaires and clinical and laboratory assessments were used to determine the frequencies of physician visits, health insu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
177
8
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 268 publications
(196 citation statements)
references
References 24 publications
10
177
8
1
Order By: Relevance
“…Only 26.7% of our cohort had an HbA 1c Ͻ7%, and 50% had an HbA 1c Ͼ8%. This is slightly worse than the mean HbA 1c of 7.8% that is reported in type 2 diabetes in NHANES III (22). These results suggest that treatment of hyperglycemia should be more diligently addressed.…”
Section: Control Of Cardiovascular Risk Factorscontrasting
confidence: 55%
See 1 more Smart Citation
“…Only 26.7% of our cohort had an HbA 1c Ͻ7%, and 50% had an HbA 1c Ͼ8%. This is slightly worse than the mean HbA 1c of 7.8% that is reported in type 2 diabetes in NHANES III (22). These results suggest that treatment of hyperglycemia should be more diligently addressed.…”
Section: Control Of Cardiovascular Risk Factorscontrasting
confidence: 55%
“…Despite continued revision of treatment goals and update to the guidelines of the ADA and other organizations regarding the management of CVD risk factors, there are no extant data, except for a small report (21) and the National Health and Nutrition Examination Study (NHANES)-III study from 1991-1994 (22), regarding the achievement of such goals and the adherence to these guidelines. Therefore, between July 1999 and July 2000, using the ADA guidelines, we assessed care provided to patients with concomitant diabetes and hypertension at two major urban academic institutions and their associated Veteran Administration (VA) Hospitals.…”
mentioning
confidence: 99%
“…(Piette et al 2003) Even when they do use outpatient care, those with lower socioeconomic status frequently encounter poor quality/insufficient patient counseling on self-care and a lack of specialist care, compromising self-care and diabetes outcomes. (Harris 2000) Other researchers have suggested that vulnerable groups maintain biomedically unconventional treatment orientations, including substituting herbal remedies for conventional medication or drawing on information from relatives rather than health care providers, that may ultimately undermine glycemic control and lead to adverse health outcomes. (Ernst 2001;Arcury et al 2003) There are some logical reasons why those groups that are disproportionately affected by diabetes may employ unconventional health strategies.…”
Section: Self-carementioning
confidence: 99%
“…Data from the Third National Health and Nutrition Examination Survey demonstrate that approximately 60% of patients with type 2 diabetes fail to achieve HbA1C levels ≤ 7 mg/dl and 60% are inadequately treated for hypertension and hyperlipidemia. 36 In a review by Phillips et al, 37 provider and system shortcomings may largely explain why patients frequently fail to achieve desired BP , cholesterol, and glycemic goals. The authors use the phrase "clinical inertia" to denote the "failure of health care providers to initiate or intensify therapy when indicated."…”
Section: Discussionmentioning
confidence: 99%